1997
DOI: 10.1089/hyb.1997.16.195
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Two Isotypically Different Antibodies Produced by a Murine Hybridoma

Abstract: A hybridoma, F31P46B, secreting monoclonal antibodies (mAbs) comprised of mu and gamma heavy chains in association with a single kappa light chain, has been characterized. This hybridoma was prepared by fusing splenocytes, derived from a BALB/c mouse immunized with Vibrio vulnificus and SP2/O-Ag-14 mouse myeloma cells. The specificity of this hybridoma was determined by ELISA screening on a large number of bacterial strains. Hybridoma cells of F31P46B were cloned by limiting dilution to an average cell density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The study proved that indeed SPRi was capable of following in real time the excretion of the expected antibodies and that it was a much easier and quicker method to confirm antibody production compared to more traditional label-based techniques [9]. Traditionally detection and quantification of single hybridoma cell excretion is a complicated procedure [10][11][12]. Recently a new fluorescence-based method was introduced, which uses metal-enhanced fluorescence.…”
Section: Introductionmentioning
confidence: 90%
“…The study proved that indeed SPRi was capable of following in real time the excretion of the expected antibodies and that it was a much easier and quicker method to confirm antibody production compared to more traditional label-based techniques [9]. Traditionally detection and quantification of single hybridoma cell excretion is a complicated procedure [10][11][12]. Recently a new fluorescence-based method was introduced, which uses metal-enhanced fluorescence.…”
Section: Introductionmentioning
confidence: 90%
“…Only a few authors have reported simultaneous secretion of IgM and IgG molecules from the same hybridoma clone. (17)(18)(19)(20) Isotype switching by B cells is highly regulated by a group of cytokines, including IL-4, IFN-g, and TGF-b. A lymphocyte B cell can only express one isotype at a time; however, during an immune response it may be exposed to combinations of stimuli that provide it with conflicting switching instructions.…”
mentioning
confidence: 99%
“…The study proved that indeed SPRi was capable of following in real time the excretion of the expected antibodies and that it was a much easier and quicker method to confirm antibody production compared to more traditional label-based techniques [98]. Traditionally detection and quantification of single hybridoma cell excretion is a complicated procedure [99][100][101]. Recently a new fluorescence-based method was introduced, which uses metal-enhanced fluorescence.…”
Section: Introductionmentioning
confidence: 90%